Analisis Akurasi Prediksi Kebangkrutan Model Altman Z-Score pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Sheilly Olivia Marcelinda; Hadi Paramu -; Novi Puspitasari - (UPT Penerbitan Universitas Jember, 2014)
This research aimed to analyse the accuracy of the Altman Z -Score bankruptcy prediction model using auditor's opinion in companies listed in Indonesia Stock Exchange. The data used in this study were secondary data obtained from the annual financial statements of manufacturing firms during 2010-2012. Selected companies listed in Indonesia Stock Exchange in 2010-2012 and having the independent auditors' report were used as a sample. The analytical method used was Altman Z -Score model and comparation between the Altman Z -Score and the auditor's opinion . Results of this study showed that the percentage of accuracy of models modified Altman Z -Score 27.96 % . It can be concluded that Altman Z -Score bankruptcy prediction model has a low level of accuracy in predicting bankruptcy of companies listed on the Indonesia Stock Exchange 2010-2012 .